1999
DOI: 10.1017/s0007114599000392
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-releasing and insulin-like activity of the traditional anti-diabetic plantCoriandrum sativum(coriander)

Abstract: Coriandrum sativum (coriander) has been documented as a traditional treatment of diabetes. In the present study, coriander incorporated into the diet (62⋅5 g/kg) and drinking water (2⋅5 g/l, prepared by 15 min decoction) reduced hyperglycaemia of streptozotocin-diabetic mice. An aqueous extract of coriander (1 mg/ml) increased 2-deoxyglucose transport (1⋅6-fold), glucose oxidation (1⋅4-fold) and incorporation of glucose into glycogen (1⋅7-fold) of isolated murine abdominal muscle comparable with 10 −8 M-insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
118
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(130 citation statements)
references
References 17 publications
3
118
0
3
Order By: Relevance
“…After 24 h maceration at room temperature (37 ºC), the mixture was heated for 30 minutes in a water bath set to 65 ºC. The extract was filtered, concentrated by heating over the water bath (65 ºC), and dried under vacuum (Gray & Flatt, 1999) with a yield of 5.9% (w/w). The extract was stored at 4 ºC and used in the experiment as needed.…”
Section: Methodsmentioning
confidence: 99%
“…After 24 h maceration at room temperature (37 ºC), the mixture was heated for 30 minutes in a water bath set to 65 ºC. The extract was filtered, concentrated by heating over the water bath (65 ºC), and dried under vacuum (Gray & Flatt, 1999) with a yield of 5.9% (w/w). The extract was stored at 4 ºC and used in the experiment as needed.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to its use as seasoning, coriander has traditionally been used for its analgesic, aphrodisiac, antirheumatic, anti-inflammatory, diuretic, antispasmodic, circulatory stimulant, and antidiabetic effects (Gray & Flatt, 1999), and more recently for its possible cholesterol-lowering (hypolipidemic) effects (Momin et al, 2012). The essential oil extracted from coriander seeds has been reported to have antimicrobial activity against both gram-negative and gram-positive foodborne pathogenic bacteria, including E. coli O157: H7, L. monocytogenes, S. aureus, B. cereus, Enterococcus faecalis, Pseudomonas aeruginosa, Klebsiella pneumoniae, Acinetobacter baumannii (Alves-Silva et al, 2013), and Candida spp.…”
Section: Optimum Amounts Of Coriander and Chive Volatile Extracts To mentioning
confidence: 99%
“…Different parts of the plant, including the fruits and the green herbs, are used for medicinal purposes such as dyspeptic complaints and loss of appetite (Blumenthal et al 2000). Pharmacological studies in animals have shown that coriander has anti-diabetic (Swanston-Flatt et al 1990;Gray and Flatt 1999), hypolipidemic, (Chithra and Leelamma 1997; and anti-cancer effects (Chithra and Leelamma 2000). Sedative-hypnotic activity of coriander seeds have been evaluated in scientific studies in mice (Emamghoreishi et al 2005).…”
Section: Introductionmentioning
confidence: 99%